Zinc Inhibits HIF-Prolyl Hydroxylase Inhibitor-Aggravated VSMC Calcification Induced by High Phosphate - Nagy, Annamária; Pethő, Dávid; Gáll, Tamás; Zavaczki, Erzsébet; Nyitrai, Mónika; Posta, József; Zarjou, Abolfazl; Agarwal, Anupam; Balla, György; Balla, József (Frontiers in Physiology, 2020)
Vascular calcification is a life-threatening clinical condition in chronic kidney disease (CKD) and is associated with reduced zinc serum levels. Anemia is another frequent complication of CKD. Hypoxia-inducible factor (HIF) stabilizers, also known as HIF prolyl-hydroxylase inhibitors (PHI), are promising candidates to treat CKD-associated anemia by increasing erythropoietin synthesis. Recent evidence suggests that HIFs play a pivotal role in vascular calcification. Our study explored feasible impacts of HIF PHI on phosphate (Pi)-induced calcification of vascular smooth muscle cells (VSMCs) and tested whether zinc might inhibit this mineralization process. Treatment of VSMCs with PHI aggravated Pi-induced calcium deposition and Pi uptake. PHI promoted Pi-induced loss of smooth muscle cell markers (ACTA-2, MYH11, SM22α) and enhanced osteochondrogenic gene expression (Msx-2, BMP-2, Osteopontin) triggering osteochondrogenic phenotypic switch of VSMCs. These effects of PHI paralleled with increased pyruvate dehydrogenase kinase 4 (PDK4) expression, decreased Runx2 Ser451 phosphorylation, and reduced cell viability. Zinc inhibited Pi-induced mineralization of VSMCs in a dose-dependent manner and also attenuated the pro-calcification effect of PHI in Pi-induced mineralization. Zinc inhibited osteochondrogenic phenotypic switch of VSMCs reflected by lowering Pi uptake, decreasing the expressions of Msx-2, BMP-2, and Osteopontin as well as the loss of smooth muscle cell-specific markers. Zinc preserved phosphorylation state of Runx2 Ser451, decreased PDK4 level, and restored cell viability. PHI alone reduced the expression of smooth muscle markers without inducing mineralization, which was also inhibited by zinc. In addition, we observed a significantly lower serum zinc level in CKD as well as in patients undergoing carotid endarterectomy compared to healthy individuals. Conclusion - PHI promoted the loss of smooth muscle markers and augmented Pi-induced osteochondrogenic phenotypic switch leading to VSMCs calcification. This mineralization process was attenuated by zinc. Enhanced vascular calcification is a potential risk factor during PHI therapy in CKD which necessitates the strict follow up of vascular calcification and zinc supplementation.